Hasan Basri SURVEI TINGKAT BODY MASS INDEX PADA GURU PENDIDIKAN JASMANI SEKOLAH DASAR SE-KECAMATAN BANTARGEBANG - Basri, Hasan (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT The purpose of this study was to determine the level of Body Mass Index on elementary school physical education teachers throughout Gebang subdistrict. The method used is descriptive quantitative techniques used in data analysis survei.Teknik fpersentase descriptive technique. The population in this research is the Master Penjas Gebang subdistrict amounting to 24 people. Tekniksampling used is total sampling where the whole population of the research sample, so the sample size in this study was 24 Orang.Instrumen research or data collection tool used in this study is measuring meter height and weight scales were then carried out mass index calculations {body with the formula BMI = weight (kg) / TB² (m)}. Based on the results of calculation and analysis of data, it can be concluded that in general the level of Body Mass Index (BMI) of elementary school physical education teachers throughout the District Bantargebang in normal circumstances. Key words: Body mass index, Teacher, Physical education